2010
DOI: 10.1177/0022034510375285
|View full text |Cite
|
Sign up to set email alerts
|

Filler Debonding & Subhybrid-layer Failures in Self-etch Adhesives

Abstract: The mechanisms behind bond degradation are still largely unknown, in particular with respect to self-etch adhesives. One-step adhesives have been especially documented with problems, such as insufficient polymerization, water-uptake and subsequent plasticization, water- and enzyme-induced nanoleakage, and/or the presence of voids due to phase-separation or osmosis. It was hypothesized that these shortcomings may weaken the adhesive layer and, as such, may jeopardize long-term bonding. In contrast to the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 22 publications
(28 reference statements)
6
86
0
7
Order By: Relevance
“…65 Apparently, the weakest zone in self-etch adhesives is located below the hybrid layer, where the adhesive penetration and/or polymerization are not sufficient to protect collagen against hydrolysis and enzymatic degradation. 6,66,67,68 Despite its superior performance as compared to other functional acidic monomers, the salt formed by 10-MDP may also degrade with time, as it is also somehow sensitive to hydrolytic dissolution. 61 According to Kim et al 67 the hydrolytic degradation of the collagen fibers still occurs at the base of the hybrid layer, characterized by voids and nanoleakage between the intact top of the hybrid layer and the mineralized dentin base, as detected by SEM and Confocal microscopy analysis.…”
Section: Chemical Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Apparently, the weakest zone in self-etch adhesives is located below the hybrid layer, where the adhesive penetration and/or polymerization are not sufficient to protect collagen against hydrolysis and enzymatic degradation. 6,66,67,68 Despite its superior performance as compared to other functional acidic monomers, the salt formed by 10-MDP may also degrade with time, as it is also somehow sensitive to hydrolytic dissolution. 61 According to Kim et al 67 the hydrolytic degradation of the collagen fibers still occurs at the base of the hybrid layer, characterized by voids and nanoleakage between the intact top of the hybrid layer and the mineralized dentin base, as detected by SEM and Confocal microscopy analysis.…”
Section: Chemical Bondingmentioning
confidence: 99%
“…12-Methacryloyloxydodecylpyridinium bromide / MDPB), 66,68,93,125,142,143 incorporated into the primer of Clearfil Protect Bond, Kuraray,(6) and dimethyl sulfoxide (DMSO), 144,145,146 correspondingly. As further efforts are required to ratify related initial encouraging results, for compiled deeper information, one should refer to Perdigão et al 40 and Tjäderhane.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%
“…Fluid movement through potential leakage pathways within the hybrid layer was called nanoleakage and water-treeing [4][5][6] . Filler de-bonding in ultra-morphology shows hydrolysis of the fillermatrix coupling 7) . On the other hand, potential internal enzymes, kinds of matrix metalloproteinase, contribute to the breakdown of collagen matrices 8) .…”
Section: Introductionmentioning
confidence: 99%
“…One-step type is not to exceed multiplestep adhesives 12) , and morphologic observation has revealed that HEMA-free adhesives give rise to phase separation 13,14) and that HEMA-containing adhesives cause hydrolysis overtime 7) . Although an adequate amount of HEMA improves the bond strength of a one-step adhesive 15) , both incomplete polymerization and existence of water are suspected to be reasons for the degradation of adhering with HEMA-containing adhesive 7) , and the degradation are caused by ingredients of manufacture rather than manipulation errors 16) . A new adhesive includes a functional additive, sodium fluoride, is thought to prevent caries.…”
Section: Introductionmentioning
confidence: 99%
“…Örnekler kesitler alınarak doğrudan su içinde, kesitler alınmadan etrafında koruyucu olduğu düşünülen mine dokusu varken indirekt olarak su içinde veya simüle pulpal basınç varlığında belli sürelerde bekletilerek bağlantının devamlılığının incelendiği çalışmalarda altı ay gibi nispeten kısa sürelerde bile bağlanma dayanımının azaldığı gös-terilmiştir. [15][16][17][18][19] Suya maruz bırakmanın bağlanma dayanımı üzerin-deki olumsuz etkisi ara yüz komponentlerinin bozulmasını sağlaması nedeniyle olabilmektedir. Bu bozulma kollajenin denatürasyonu veya degrede olmuş veya yeterli polimerize olmamış rezinin salınması şeklindedir.…”
Section: Discussionunclassified